(Un)precedented times? An interview by Julie Parle with Emeritus Professor Howard Phillips (Historia, 2021)
Covid-19 has changed our present profoundly. It is too early to assess the extent to which it will change our future. Should it change our view of our past? Do we live in (un)precedented times? These are questions I put to Professor Howard Phillipswhose deep research into the history of epidemics and pandemics in South Africa has always been pertinent, perhaps never more so than today’s time of Covid-19. For more than 40 years his research has highlighted, arguably, one of the most importantevents in our history; yet, paradoxically, it is one that has been largely forgotten: the ‘great’ or ‘Spanish’ influenza epidemic of 1918-1919.